Student Engagement for Students of Psychology Study Program, Universitas Indonesia Membangun - Pratidina Ekanesia; Prinska Damara Sastri; Hanifah Jauhary, Zakiyah Aulia Sabrina (Westscience Press, 2023)
The highest level of completing school education is tertiary education. Not many students do not continue their education to university, so they choose to look for work and some choose to work to be able to pay for college. With so many students who are not only preoccupied with lecture matters but participate in activities outside of lecture activities such as participating in organizations both on and off campus and working part-time. But in reality, they often have difficulty dividing their time. This study aims to determine the perception of the situation that keeps them involved in the learning process (student engagement) in Inaba University's Psychology Study Program students. Student engagement consists of two dimensions, namely campus engagement and class engagement. The research was conducted on 87 students of the INABA University Psychology Study Program. The measuring tool used is Student Engagement Scale from Gunuc & Kuzu. The research results show that student engagement INABA University Psychology Study Program students are at a low level of 59%. In addition, dimensions of campus engagement and class engagement INABA University Psychology Study Program students, both of whom are at a low level.